Video Based Steganography (Motion Vector Steganography) - Della Patresya Sitohang; Purba Lamdippos Hendry Parmadi; Vinela Br Sitepu; Wilhelmus Wanzerhasratman Gulo (SEAN Institute, 2023)
Steganography is a technique for hiding information in digital media so that it cannot be detected by third parties. One effective steganography method is Motion Vector Steganography (MVS), which utilizes motion vectors in video compression to insert secret messages. This study implements the Least Significant Bit (LSB) and Most Significant Bit (MSB) methods on motion vectors in videos to insert messages with minimal changes in visual quality. The results of the analysis show that the LSB method has little impact on video quality, while the MSB method is more resistant to steganalysis detection. However, there are challenges such as changes in file format and video size that need to be considered. This study provides insight into the application of video-based steganography and its potential development in the field of information security.